Accommodating Classroom Activities to EFL Learners’ Multiple Intelligences - Dung, Nguyen Thi; Tuan, Luu Trong (Mediterranean Journal of Social Sciences, 2011)
Gardner’s Multiple Intelligences theory has been among the theories innovating English Language Teaching since the period of the 70s and 80s. In this paper, the literature of Multiple Intelligences theory and its benefits on learners’ learning cognition, motivation, interaction and achievement are reviewed. Besides that, types of language learning activities and classroom activities to accommodate to learners’ Multiple Intelligences are presented. Keywords: Multiple Intelligences theory, cognition, motivation, interaction, achievement, classroom activities.